2020
DOI: 10.1093/ofid/ofaa547
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Immune Surveillance in Allogenic Stem Cell Transplant Recipients: Are Whole Blood–Based Assays Ready to Challenge ELISPOT?

Abstract: We compared the feasibility of four CMV- and Aspergillus-reactive T-cell immunoassay protocols in allogenic stem cell transplant recipients. While ELISPOT performed best overall, logistically advantageous whole blood-based assays performed comparably in patients with less severe lymphocytopenia. CMV-induced interferon-gamma responses correlated strongly across all protocols and showed high concordance with serology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, the WB-ELISA protocol showed superior robustness to pre-analytic delays compared with previously published data for PBMC-based assays (including ELISA) to detect A. fumigatus-specific T-cell activation [12,13]. A recent study by our consortium further revealed an overall promising performance of WB-ELISA in allogenic hematological stem cell transplant recipients [57]. Specifically, high technical reliability and good concordance of IFN-γ response to CMV phosphoprotein 65 with CMV serostatus and reactivation was seen in patients with >800 lymphocytes per µL of peripheral blood.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Additionally, the WB-ELISA protocol showed superior robustness to pre-analytic delays compared with previously published data for PBMC-based assays (including ELISA) to detect A. fumigatus-specific T-cell activation [12,13]. A recent study by our consortium further revealed an overall promising performance of WB-ELISA in allogenic hematological stem cell transplant recipients [57]. Specifically, high technical reliability and good concordance of IFN-γ response to CMV phosphoprotein 65 with CMV serostatus and reactivation was seen in patients with >800 lymphocytes per µL of peripheral blood.…”
Section: Discussionmentioning
confidence: 74%
“…Lastly, the patient cohort for validation of the assay in the present study was limited in size and did not cover patients with proven or probable invasive aspergillosis due to a lack of appropriate samples. Nonetheless, the technical reliability and high discriminatory power observed in the present study and the solid performance of our WB-ELISA system in allogenic stem cell transplant recipients [57] encourage future multi-center evaluation in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 76%